O protagonismo judicial e a ilegitimidade democrática da judicialização da política - VERBICARO, Loiane da Ponte Souza Prado (Universidade Federal do Pará, 2014)
This research is aimed at analyzing the Judiciary Power in a context wherein it acts as an agent amplifying its political dimension which brings about, as a consequence, a peculiar and unheard of type of public avenue of democratic participation. It has to do with the opening of a public space arising out of the augmentation in judicial activity, by way of an increased expansion of the law, its procedures and institutions over politics and societal framework of modern-day life, which allows for ampler access of citizens to the power circles. Such changes in the political and institutional environment made it possible for a more extended insertion of the Judiciary Power in essentially political matters, which came to gain widespread acceptance as ´judicialization´ of politics and has been expressed by a magnified importance and actual participation of the Judiciary Power in social, political and economical life. Such phenomenon, typical of consolidated democracies, derived from conditioning variables and peculiarities experienced in political, economical and social order and brought about visible consequences in Brazilian democracy. The consequences of said ´judicialization´ process of politics over the democratic opening vary in accordance with the analytical focus being established as the theoretical reference point: the substantive law-based current, as a defender of a more participatory Judiciary Branch; as opposed to the procedural law-based current, which emphasizes majority processes for building of political will in detriment to judicial ways.